A Straightforward and Efficient Approach to the Synthesis of 3-Cyano-Coumarine Derivatives - Asmaa Kebaili; Fatima Belhadj; Zahira Kibou; Julio A. Seijas; M. Pilar Vazquez Tato; Noureddine Choukchou-Braham (Chemistry Proceedings, 2024)
Oxygen heterocycles represent a significant category of organic molecules that are abundant in nature and important in scientific research due to their use in diverse applications across various fields. Coumarins, in particular, comprise a wide range of compounds known for their extensive biological activities, making them invaluable in medicine, pharmacology, cosmetics, and the food industry. The biological effects and potential applications of coumarins are closely tied to their specific chemical structures. As a result, researchers frequently engage in the synthesis of coumarin derivatives to explore their varied uses. In this context, we focused on the synthesis of 3-cyano-coumarin and its derivatives. This study introduces a simple synthesis method that enables the efficient and accessible production of these structures under mild, environmentally friendly conditions, yielding excellent results.